EXAMINATION OF ISOKINETIC STRENGTH RATES OF KNEE JOINT (H/Q) IN FOOTBALL PLAYERS - YILMAZ, Ali Kerim; KABADAYI, Menderes; MAYDA, M. Hakan; BIRINCI, M. Ceyhun (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The purpose of this study is to examine the isokinetic strength rates of knee joint (H/Q) in football players. 30 males (15 football players, 15 controls) were included in the research who were studying in YaÅŸar DoÄŸu Sports Sciencies faculty of Ondokuz MayÄ±s University. The position, age and dominant leg information of the subjects were determined by filling in personal information forms given to the subjects. Body mass index measurements were recorded with a Gaia 359 plus body analyzer and H/Q force rates were measured and recorded with a Humac Norm Cybex Brand computer controlled isokinetic dynamometer at angles of 60osn-1, 180osn-1 and 240osn-1. For the statistical analysis of the data used SPSS 22.0 software was used. Independent t-test was applied for the analysis of football player-control group and dominant leg results. In addition, one-way variance analysis and LSD test were used for repeated measures to compare football players according to their positions. Statistical results were evaluated at 95% confidence interval and p <0.05 significance level. When we look at the descriptive information between the two groups in our study; There was a significant difference between age, body weight and sport ages, but no significant difference was observed in other parameters. When the H/Q power ratios at angular velocities of 60osn-1, 180osn-1 and 240osn-1 were examined, no significant difference was found between the dominant-nondominant force ratios and footballer positions between the two groups. As a result, when H/Q power ratios of footballer and control group are examined; There was no significant difference between the two groups when dominant-nondominant strength ratios and soccer player positions were compared.